Light Microscopic Investigation of Developing Rat Teeth After Atenolol Drug Administration (Experimental Study) - Asmaa S Al-Douri (University of Mosul, College of Dentistry, 2011)
Aims: To investigate the effect of atenolol drug on the formation and development of rat dentition of rat (histologically and histochemically). Materials and Methods: Albino Wister rats were divided into two main groups,. The control group and experimental group, each consisted of (9) pregnant rats, giv-en 1 ml distilled water and 10 mg atenolol (powder) suspended in 1ml distilled water , orally , as a single dose, respectively from 12 - 18 day of gestation, after delivery of pregnant rats, 36 newborn were selected to be scarified at ages 1, 5. and 10 post nataly from each group. The specimens were prepared for processing and stained with H&E and alcian blue stains. Results: The treated groups showed obvious histological changes: delay in tooth germ formation, increase blood vascularity, disorganization of ameloblast and odontoblast cells, and delay in glycosaminoglycan synthesis. Conclusions: Atenolol drug delay the rat tooth development causing abnormal odontogenic changes and inhibits glycosaminoglycan synthesis.